The promise and perils of biomarker testing in gynecologic cancers - Fitch, Katherine C.; Previs, Rebecca A.; Moss, Haley A. (Gynecologic oncology, 2025)
•Biomarker testing is crucial for personalized medicine, offering benefits in treatment precision, prognosis and outcomes.•Overcoming barriers to biomarker testing utilization is essential for equitable access and optimal care for all patients.•Implementing policy change, clinical pathways, and educational programs can enhance the effective use of biomarker testing.